Pengaruh Pemahaman Hadis Keutamaan Ilmu terhadap Minat Belajar Mahasiswa - Muhammad Raihan Al Farez; Irfan Yuhadi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Differences in students’ levels of learning interest are often associated with their understanding of religious values, one of which is the understanding of hadiths concerning the virtues of knowledge. Hadiths emphasizing the virtues of knowledge are believed to stimulate interest in the learning process. This study aims to examine the influence of students’ understanding of hadiths on the virtues of knowledge on their learning interest at STDI Imam Syafi’i Jember. This research employed a quantitative approach with a correlational design. A total of 130 students were selected as respondents using simple random sampling. The research instruments were tested for validity and reliability, yielding Cronbach’s alpha values of 0.838 for the variable of understanding the hadiths on the virtues of knowledge and 0.884 for the learning interest variable. The normality test using Shapiro–Wilk produced a value of 0.097, indicating that the data were normally distributed, while the heteroscedasticity test showed a significance value of 0.968, confirming that the regression model was appropriate for use. The regression analysis revealed a significance value of p = 0.001 and a coefficient of determination (R²) of 0.362. This indicates that understanding the hadiths on the virtues of knowledge has a positive influence of 36.2% on students’ learning interest, while the remaining 63.8% is influenced by other factors. These findings affirm that understanding the values contained in hadiths on the virtues of knowledge plays an important role in enhancing students’ learning interest.